Overview of Work Stress Based on Work Divisions in The Health Department X - Haidar Rifqi Albadii; Izza Hananingtyas (International Conference on Sustainable Health Promotion, 2025)
Work stress is a serious challenge in the health sector, affecting productivity and service quality. This study aims to analyze the level of work stress by division in the Health Office of City X using a quantitative cross-sectional approach involving 115 respondents in 2025. The results show that 53% of employees experience work stress, with disparities across divisions: Disease Prevention and Control (P2P) recorded the highest prevalence (66.7%), followed by Health Services (60%), and Public Health (54.2%), while Health Resources (SDK) had the lowest rate (36%). Employees with less than 8 years of service were more prone to stress (59.6%) compared to those with ≥8 years of experience (48.5%). Task complexity showed a unique pattern, with high stress levels in both low (57.1%) and high (54.8%) complexity tasks, indicating that both monotonous and challenging work carry risks. These findings highlight the importance of division-based interventions, such as workload redistribution in P2P and stress management training for new employees. The study recommends a periodic assessment system and mental health protection policies in accordance with Law No. 17 of 2023. This research contributes to occupational health literature by emphasizing a contextual approach to stress mitigation.